A critic in the “post-artistic era”. About the concept of Jerzy Ludwiński on the example of the activity of Gallery “Pod Moną Lisą” - Góźdź, Szymon (Death of the Critic: Participatory Culture and the Transformations of Criticism in the 20th and 21st Centuries, 2022)
The article contains general characteristics of the Gallery “Pod Moną Lisą” in relation to the person and pioneering assumptions of Jerzy Ludwiński. I present the most important facts about the creation, program and functioning of the Gallery; the reactions and a general calendar of exhibition activities. I assume that the fact of the existence and success of the Gallery, in addition to Ludwiński’s titular contribution, largely determined the specificity of then Wrocław. I’m also trying to determine the importance and importance of the novel variant of Ludwiński’s artistic critique successfully implemented by the Gallery, both during its period of operation and after its closure.